Perencanaan Trategis Peningkatan Kualitas dan Kuantitas Tenaga Kependidikan di Kabupaten Boven Digoel - , Marius Aiman, S.Sos ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In this study, the problem is what the obstacles that hinder in planning and improving how the strategies of teachers and education agencies to plan and increase the number of teachers (HR) in Kabupeten Digoel?. Implementation of Education in the district Digoel has not been seen going well, there are obstacles in the face by the Government, in this case the Department of Education as well as responsible paprties penggelolah in the planning of Management Education Secondary School level, the problem is human resources or teacher, with Thus the strategy is education must always be based on the concept of growth, development, renewal, and continuance so that education should be professionally managed and able to meet the HR needs of each school The method used there are two library research, research conducted by reading and reviewing books, literature, laws and regulations, sources from the internet, and other articles relevant to the discussion of a thesis to obtain an understanding theoretically as a basis for data collection, and field research, this study carried out by conducting surveys directly to the district government education offices Digoel mainly through technical interviews with the parties or employees concerned and to study the planning of teachers in the District Education Office Digoel Education agencies to plan strategies and increase the number of teachers (HR) in Kabupeten Digoel through a learning process that is known by several terms that have the same meaning, so often people get confused to differentiate. These terms are: (1) learning approach, (2) learning strategies, (3) teaching methods, (4) techniques of learning, (5) learning tactics, and (6) learning model. The following will set out these terms, hoping to give kejelasaan about the use of the term. Learning strategy setting objectives vary, but all point to the same essence, that: (1) objective is the achievement of learning or behavioral changes in students' competence after participating in learning activities (2) the objectives formulated in the form of a statement or a specific description. It is interesting to underlined that the formulation of learning objectives should be embodied in written form. This implies that each lesson plan should be made in writing (written plan) that can be used as an archiving system and provides a basis in the future.